(untitled) - Kubasakova, Iveta (Doprava a spoje, 2012)
Paper is devoted to the characteristics of both technologies and their advantages and disadvantages of the application in the supply of manufacturing companies. The developments of automotive and electronics industry has a clear impact on the supply of these goods manufacturing companies. One of the most widely used technologies could include technology, Just-in-time (JIT), Kanban system, and the else systems. JIT technology innovation was technology JIS Just in Sequence. The suppliers under JIS regulate its own production plan so as to be able to deliver their products at the right time in right quantity at the right place and in the desired sequence - the sequence.